ASSESMENT OF MICROBIAL DIVERSITY IN GASTRO INTESTINAL TRACT OF ESTUARINE FISHES - K.R. BEULA RANI,; M. MURUGAN, (International Journal of Pharma and Bio Sciences, 2015)
Bacterial strains were isolated from the gastrointestinal tract of seven fishes collected from Thengapattinam estuary of Kannyakumari District, Tamil Nadu. The fishes were identified by standard keys. An intestinal contents were removed aseptically from the fishes, from that bacterial flora was isolated by serial dilution-agar platting method. In this present study a total of 12 bacterial gut flora was identified by studied their cultural, morphological and biochemical studies viz. Escherichia coli, Streptococcus sp, Staphylococcus sp, Micrococcci sp, Pseudomonas aeroginosa, Salmonella sp, Serratia sp, Shigella sp, Vibrio alginolytic, Vibrio parahaemolytics, Corynebacterium sp and Proteus sp. Among these, E. coli., Staphylococcus and P. auroginosa were found as dominant gut flora.